Protocol for generating liver metastasis microtissues to decipher cellular interactions between metastatic intestinal cancer and liver tissue - Maria Lamprou; Ana Krotenberg Garcia; Saskia Jacoba Elisabeth Suijkerbuijk (STAR Protocols)
Summary: Cell competition is a quality control mechanism that promotes elimination of suboptimal cells relative to fitter neighbors. Cancer cells exploit these mechanisms for expansion, but the underlying molecular pathways remain elusive. Here, we present a protocol for generating matrix-free microtissues recapitulating cellular interactions between intestinal cancer and hepatocyte-like cells using microscopy or transcriptomics/proteomics. We describe steps for generating and differentiating liver progenitor organoids and microtissue formation. We then detail procedures for immunofluorescence staining, mounting microtissues, and sorting cells.For complete details on the use and execution of this protocol, please refer to Krotenberg Garcia et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.